World Wide Web applications in South Africa - Raitt, David I. (Electronic library ;, 2007)
This ebook contains a group of papers selected from the 2006 ZA-WWW conference, which is endorsed as a Regional Conference by the IW3C2. The papers selected not only show the scope and breadth of research being undertaken on the World Wide Web, but perhaps more importantly they also demonstrate the that South African ideas and activities play no small role in the development and use of the Web. To this end, Butler discusses the growing phenomena of phishing and how we should be protecting ourselves; in the same vein Etsebeth discusses malware and cyber risk, while Seymour and Naasden look at th.